Characterization of Novel Aptamers Specifically Directed to Red-Spotted Grouper Nervous Necrosis Virus (RGNNV)-Infected Cells for Mediating Targeted siRNA Delivery - Zhou, Lingli; Wang, Shaowen; Yu, Qing; Wei, Shina; Liu, Mingzhu; Wei, Jingguang; Huang, Youhua; Huang, Xiaohong; Li, Pengfei; Qin, Qiwei (Frontiers in Microbiology, 2020)
Nervous necrosis virus (NNV) causes viral nervous necrosis, the most devastating disease in more than 50 fish species worldwide, with massive mortality rates up to 100%, resulting in great economic losses to mariculture. However, few methods are available for the efficient diagnosis and treatment of viral nervous necrosis. Aptamers are molecular recognition ligands characterized by their remarkably high specificity and affinity, great stability, and ease of synthesis, and have been widely studied in application of diseases diagnosis and therapies. In this study, we generated three aptamers against red-spotted grouper nervous necrosis virus (RGNNV)-infected grouper brain (GB) cells using the Cell-SELEX (cell based-systematic evolution of ligands by exponential enrichment) technology. The selected aptamers formed stable stem-loop structures, and could specifically recognize RGNNV-infected GB cells, with calculated dissociation constants (Kd) of 27.96, 29.3 and 59.5 nM for aptamers GBN2, GBN10, and GBN34, respectively. They also recognized RGNNV-infected brain tissues. The three aptamers were nontoxic and showed antiviral activities both in vitro and in vivo. Florescence microscopy and flow cytometry also demonstrated that aptamer GBN34 could be efficiently and specifically internalized into RGNNV-infected GB cells. The targeted cellular delivery of aptamer-small interfering RNA (siRNA) conjugates remarkably inhibited RGNNV infection in GB cells. The efficiency of the aptamer-based targeted delivery system was about 75% reduction in infection after 48 h, which was similar to that of transfection. These aptamers have great potential utility in the rapid diagnosis and inhibition of RGNNV infection in mariculture.